The value of posttreatment CA125 and PET/CT in predicting prognosis of epithelial ovarian cancer (Annals of Medical Research, 2021)
Aim: To investigate the association between post treatment F-18 fluorodeoxyglucose (FDG) positron emission tomography/ computed tomography (PET/CT) and post treatment cancer antigen 125 (CA125) results and overall survival (OS) of patients with epithelial ovarian cancer (EOC).Material and Methods: Survival was analyzed with Kaplan-Meier, Log-Rank and Cox proportional-hazards regression analyses. All cases and PET+ cases were evaluated separately. In addition, PET and CA125 results were evaluated together in the overall case group, and a survival analysis was made for the four defined groups.Results: The mean age of the 112 EOC-diagnosed patients was 54.9±0.9 years. Based on the PET/CT results, 48 patients were PET-and 64 patients were PET+; and 59 patients were CA125- and 53 patients were CA125+. In the overall case group, OS was found to be significantly shorter in advanced stage patients when compared to the early stage patients, in the CA125+ patients when compared to the CA125- patients, and in the PET+ patients when compared to the PET- patients. A univariate analysis revealed a significant association between stage, CA125 and PET results, and OS. In a multivariate analysis, the association between stage and CA125 with OS was maintained, although the PET results were not significant. When the PET and CA125 results were evaluated together, the OS was significantly shorter in the CA125+/PET+ group than in the CA125-/PET-and CA125-/PET+ groups. In the PET+ group, CA125 and the time from diagnosis to positive PET result were identified as independent prognostic factors.Conclusion: Although OS had a tendency to be poorer in PET+ cases than negative cases, the PET results were not established asan independent prognostic factor for survival. Our findings suggest that the post treatment CA125 value is more beneficial than PETresults for the estimation of prognosis in EOC.